Bilateral Brachial Plexus Palsy in Restless Patient - Malshikare, Vijay A. (Journal of Hand and Microsurgery, 2019)
We present a case of bilateral infraclavicular brachial plexus palsy at terminal branching level in organophosphorus poisoning patient. The complication occurred during treatment. The patient was tied to the side railing of the bed with bandage as patient was restless. It is an acceptable practice so that the restless patient does not inflict injuries when he is restrained on the bed. Failure to recognize the significance of this will lead to patient injury.
Keywords: organophosphorus poisoning; brachial plexus injury; peripheral nerves